Late quaternary paleosol records from sutropical (38°S) to tropical (16°S) South America and palaeoclimatic implications - Zech, Wolfgang; Zech, MIchael; Zech, Roland; Peinneman, Néstor; Morras, Hector; Moretti, Lucas Martin; Ogle, Neil; Fucks, M.; Kalim, R.M.; Schad, P.; Glaser, B. (Elsevier, 2025)
Loess and palaeosols in the subtropical lowlands of South America (∼23–38°S) have a large potential to serve as archives of Late Quaternary environmental and climate changes. At present, mean annual precipitation generally decreases from N to S and from E to W, though with a complex seasonal pattern with austral summer rainfall related to the monsoonal circulation and with austral winter rainfall related to the SE-trades. In this paper, we present results of multiproxy geochemical analyses from three representative eolian/alluvial soil profiles along a S–N transect aiming at the reconstruction of past climate changes: (i) profile “Chasico” at the southern border of the subtropics (38°S), (ii) “D4” in Misiones at the northern border of the subtropics (27°S), and, for comparison, (iii) “Laguna Sucuara” in the savannas of the Bolivian lowlands (16°S). Our results show that before ∼16 ka BP, conditions were likely very cold and dry. Except for in “D4”, loess or soils are not preserved due to rather scarce vegetation cover and resultant deflation. In “Chasico”, accumulation of sands (directly overlying the Tertiary) starts only during the Late Glacial, indicating increasing temperatures and increased monsoonal precipitation (coinciding with the “Tauca” wet phase on the Altiplano). In “D4”, a palaeosol is preserved below the Late Glacial sediments and the deflation hiatus. This palaeosol is dated to ∼40 ka BP and documents an earlier, but less intensive (southward reaching) phase of monsoonal precipitation (“Inca Huasi” on the Altiplano). Whereas the seasonality during the Late Glacial seems to have been very pronounced, conditions for organic matter production and preservation became much more favourable at “Chasico” and “D4” during the Early Holocene. We suggest that extra-tropical winter precipitation played a more important role than before and than today. Between ∼7.5 and 3 ka BP, the expansion of C4 plants along the S–N transect suggests increasing aridity, probably due to a weakening of the extra-tropical circulation in combination with a relatively weak monsoonal circulation. Only after ∼3 ka BP climate became more humid again due to the re-strengthening of the monsoon.